Citizens Against Corruption: Report from the Front Line - Landell-Mills, Pierre (Matador, 2013)
Citizens Against Corruption: Report From The Front Line tells the stor y of how groups of courageous and dedicated citizens across the globe are taking direct action to root out corruption. It shows how people a re no longer prepared to accept the predatory activities of dishonest officials and are challenging their scams. It draws on over 200 unique case studies that describe initiatives undertaken by 130 civil societ y organisations (CSOs) which engage directly with public agencies to s top the bribery and extortion that damages peoples' lives and obstruct s social and economic progress. This book challenges the notion that, at best, civil society can only have a marginal impact on reducing cor ruption and argues that aid donors need to radically rethink their ass istance for governance reform. Part 1 analyses the role citizens can p lay in fighting corruption and promoting good governance and briefly t ells the story of the Partnership for Transparency Fund (PTF). Part 2 presents studies of India, Mongolia, Philippines, and Uganda - each wi th its unique history and distinctive circumstances - to illustrate ac tivities undertaken by CSOs to root out corruption, including the tool s and approaches that are being used to build pressure on corrupt publ ic agencies to become transparent and accountable. Part 3 addresses ke y themes - strengthening the rule of law, putting in place effective n ational anti-corruption strategies and institutions, making public buy ing and selling honest, promoting grassroots monitoring of public expe nditures and the provision of public services, mounting media campaign s to expose and defeat corruption, and empowering ordinary citizens to keep watch on what actually happens at the point of delivery of publi c services. Part 4 is a summary of lessons learnt and explores the pot ential, as well as the risks and limitations, of civic activism in a w orld where greed and dishonesty is the norm. Finally, the book explore s the opportunities and dangers faced by aid donors in supporting loca l CSOs and charts a way forward. Citizens Against Corruption: Report F rom The Front Line will be of interest to staff working in CSOs and ai d agencies, policy analysts and researchers concerned about corruption and poor governance.